Enhancing Social Competence for Disadvantaged Youth in Pre-Vocational Education: Model Development Through Design-Based Research - Ida Kristina Kühn (European Research Network Vocational Education and Training (VETNET), 2017)
This study investigates the enhancement of social competence for disadvantaged young people based on the example of the "Werkschule Bremen" educational course. Theoretical approaches to social competence as a learning outcome are mainly based on the model of social information processing, although the meaning of both practical and experience-oriented approaches is constantly evolving. Taking the specific contextual conditions into account, this study combines qualitative and quantitative methods within the design-based research methodology in order to determine how a location-independent didactical concept to enhance social competence could be created as well as which comparable impacts on the participants' social competence can be verified. The results show that a basic didactical concept is feasible, while the teaching and learning environment has a huge impact on the comparability. It is also clear that the students' motivation to participate depends on both their own and their teachers' interest as well as the teachers' capacity to facilitate safe relationships. As a core result, this study delivers a didactic model that is based on target-controlled experience-oriented learning environments on the practical side and the social information processing approach on the theoretical side.